2002
DOI: 10.1002/ccd.10095
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and cerebral angiography performed by cardiologists: Cerebrovascular complications

Abstract: The management of extracranial carotid artery disease is primarily concerned with the prevention of acute stroke. In order to understand the current risks of carotid angiography performed by interventional cardiologists, we undertook a retrospective study to determine the neurologic complications in patients who underwent selective cerebral angiography. All patients undergoing studies that were limited to diagnostic aortic arch angiography and selective four-vessel cerebral angiography in the cardiac catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…218 -225 Substantially higher rates of stroke have been reported with diagnostic angiography in some series, most notably in ACAS, 71 in which the incidence was 1.2% because of unusually frequent complications at a few centers. Complication rates in other studies have been substantially lower, 226 and most authorities regard a stroke rate Ͼ1% with diagnostic angiography as unacceptable. 227 Angiography may be the preferred method for evaluation of ECVD when obesity, renal dysfunction, or indwelling ferromagnetic material renders CTA or MRA technically inadequate or impossible, and angiography is appropriate when noninvasive imaging studies produce conflicting results.…”
Section: Catheter-based Contrast Angiographymentioning
confidence: 95%
“…218 -225 Substantially higher rates of stroke have been reported with diagnostic angiography in some series, most notably in ACAS, 71 in which the incidence was 1.2% because of unusually frequent complications at a few centers. Complication rates in other studies have been substantially lower, 226 and most authorities regard a stroke rate Ͼ1% with diagnostic angiography as unacceptable. 227 Angiography may be the preferred method for evaluation of ECVD when obesity, renal dysfunction, or indwelling ferromagnetic material renders CTA or MRA technically inadequate or impossible, and angiography is appropriate when noninvasive imaging studies produce conflicting results.…”
Section: Catheter-based Contrast Angiographymentioning
confidence: 95%
“…In asymptomatic patients in the ACAS trial, stroke occurred in 1.2% of patients after angiography (22). More recent studies reported neurological complication rates in less than 1% of patients, suggesting that the risk may be lower than previously reported (90,91). Possible explanations for these differences are improvements in equipment, technique, and operator experience; monitoring of cathetertip pressure during angiography; and use of procedural heparin and antiplatelet agents.…”
Section: Carotid Angiographymentioning
confidence: 71%
“…Substantially higher rates of stroke have been reported with diagnostic angiography in some series, most notably in ACAS (71), in which the incidence was 1.2% because of unusually frequent complications at a few centers. Complication rates in other studies have been substantially lower (226), and most authorities regard a stroke rate Ͼ1% with diagnostic angiography as unacceptable (227). Angiogra- phy may be the preferred method for evaluation of ECVD when obesity, renal dysfunction, or indwelling ferromagnetic material renders CTA or MRA technically inadequate or impossible, and angiography is appropriate when noninvasive imaging studies produce conflicting results.…”
Section: Catheter-based Contrast Angiographymentioning
confidence: 98%